Studi Komparatif Model Pembelajaran Reciprocal Teaching dengan Bamboo Dancing - roikhatul machbubah machbubah (JoEMS (Journal of Education and Management Studies), 2020)
ABSTRACT This study aims to describe: 1) How is the Reciprocal Teaching learning model towards learning outcomes of Islamic Culture History class XI MA Rahmat Said Bongkot Peterongan Jombang.2) How is the Bamboo Dancing learning model towards learning outcomes of Islamic Culture History class XI MA Rahmat Said Bongkot Peterongan Jombang.3) What is the difference from the Reciprocal Teaching Learning Model with Bamboo Dancing to the learning outcomes of students in Islamic Culture History Class XI MA Rahmat Said Bongkot Peterongan Jombang .. This type of research is field research (Fled Research) through a correlational quantitative approach. The method of determining the subject takes all Class IX at MA Rahmat Said Bongkot Peterongan Jombang as a research respondent totaling 20 students. While the method I use in this study is a quantitative method, with data collection techniques including: observation, interviews, documentation and questionnaires. Data analysis using the formula t-test separated variance The hypothesis proposed is H1: there is a comparison of the Reciprocal Teaching learning model and Bamboo Dancing science at MA Rahmat Said Bongkot Peterongan Jombang was declared accepted. Keywords : Model Reciprocal Teaching, and Model Bamboo Dancing